Invasive Forest Insects, Introduced Forest Trees, and Altered Ecosystems Ecological Pest Management in Global Forests of a Changing World - Paine, Timothy D.; Paine, Timothy D. (Springer Netherlands : Imprint: Springer, 2006)
Demand for timber and fibre continues to grow and is being met by increased reliance on plantation forestry. Many of the plantations that are being grown around the globe are non-native species that have characteristics of rapid growth and good commercial qualities. In some cases, the high rates of production are a result of the absence of native herbivore and diseases. This limited pest status is threatened as pest species move around the globe. At the same time there is concern about threats of these non-native plantation species on native communities and the impact of changing climates on forest productivity. This volume explores many of these issues for the first time.